2015
DOI: 10.1115/1.4031550
|View full text |Cite
|
Sign up to set email alerts
|

Co-Kriging Method for Form Error Estimation Incorporating Condition Variable Measurements

Abstract: The form error estimation under various machining conditions is an essential step in the assessment of product surface quality generated in machining processes. Coordinate measuring machines (CMMs) are widely used to measure complicated surface form error. However, considering measurement cost, only a few measurement points are collected offline by a CMM for a part surface. Therefore, spatial statistics is adopted to interpolate more points for more accurate form error estimation. It is of great significance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…They found that chip serration causes microwaves on machined surfaces, which increases machined surface roughness. In addition, Du and Fei conducted a series of studies on surface topography classification and measurement in conventional milling [14][15][16][17]. However, there has been no relevant research involving UPRFC.…”
Section: Introductionmentioning
confidence: 98%
“…They found that chip serration causes microwaves on machined surfaces, which increases machined surface roughness. In addition, Du and Fei conducted a series of studies on surface topography classification and measurement in conventional milling [14][15][16][17]. However, there has been no relevant research involving UPRFC.…”
Section: Introductionmentioning
confidence: 98%
“…The literature on spatial statistics-based calibration methods is sparse. A method based on Co-Kriging models to estimate the errors of the surface form not only concerning spatial correlation but also concerning the influence of machining conditions is developed in [46]. A spatial statistical method to design adaptive inspection plans for the geometric control of mechanical parts with CMSs is presented in [47].…”
Section: Introductionmentioning
confidence: 99%
“…Spatial interpolation is one possible solution to acquiring high-resolution surface data with relatively low cost [1,7,8]. When using this type of technique, the value of properties, e.g., surface heights and pixel RGB values, at unobserved locations is estimated with measurement data from its vicinal sampled locations based on spatial models.…”
Section: Table Of Contents Introductionmentioning
confidence: 99%